Conductivity in nonpolar media: Experimental and numerical studies on sodium AOT-hexadecane, lecithin-hexadecane and aluminum(III)-3,5-diisopropyl salicylate-hexadecane systems - Peschka, Dirk; Schmidt, Jochen; Wagner, Barbara; Bänsch, Eberhard; Münch, Andreas; Peukert, Wolfgang; Prignitz, Rodolphe (Journal of Colloid and Interface Science, 2012)
The conductivity behavior of doped hydrocarbon systems is studied by applying impedance spectroscopy. In the case of 3,5-diisopropyl salicylato aluminum (III) the charge carriers are formed by dissociation of the compound and their concentration is proportional to the square root of the solute concentration. In hydrocarbon systems that consist of micelle forming compounds (sodium AOT/lecithin) a linear dependence of charge carrier concentration on solute concentration is observed in the concentration regime where micelles are present. The conduction mechanisms are studied by numerical solution of a Poisson-Nernst-Planck system that describes the charge transport. We follow two different approaches to extract the degree of micelle dissociation from the impedance data. Firstly, by computing the response of a linear approximation of the Poisson-Nernst-Planck model, and secondly by computing the fully nonlinear response from direct numerical simulations using finite elements. For high and moderate frequencies both approaches agree very well with the experimental data. For small frequencies the response becomes nonlinear and the concept of impedance fails. Furthermore, the numerically computed values for the degree of dissociation are of the same order of magnitude as the values obtained with classical formulas, but still differ by a factor of about 1/3. The direct numerical simulation allows new insight into the conduction mechanisms for different frequency regimes. © 2012 Elsevier In
Keywords: Degree of dissociation; Direct numerical simulation; Electrochemical impedance spectroscopy; Finite element analysis; Poisson-Nernst-Planck model; Reverse micelles

Numerical simulation of suspension induced rheology - Prignitz, Rodolphe; Bänsch, Eberhard (Kybernetika, 2010)

Particulate flows with the subspace projection method - Prignitz, Rodolphe; Bänsch, Eberhard (Journal of Computational Physics, 2014)
A novel finite element method for the 3d simulation of (many) particles in a Newtonian carrier liquid is presented. The methods features the celebrated one domain approach, a subspace projection method to account for the rigid body motion within the particles and operator splitting. Combined with local mesh refinement the method results in a fast and accurate, though conceptually simple to implement algorithm. Validation is achieved using the sedimentation of one particle and comparing the resulting drag coefficient with theoretical and experimental results. Furthermore, a viscometer is considered, where the effective viscosity of a particle laden fluid is compared with analytic results.